STRUCTURE OF THE SEAGRASS COMMUNITY IN KARANG TIRTA PADANG BEACH: STRUKTUR KOMUNITAS LAMUN DI PERAIRAN PANTAI KARANG TIRTA PADANG - Firda Az Zahra; Aulia Azhar; Daimon Syukri; Ririn Fatma Nanda; Chairul Chairul; Indra Junaidi Zakaria (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2022)
Seagrass bed on Karang Tirtas's coast consist of two species of seagrass namely Thalassia hemprichii and Enhalus acoroides. Thalassia hemprichii is the most dominating species with a frequency to be found about 96,3% while the frequency of Enhalus acoroides is 3,7%. Seagrass has ± 14 hektar distribution area with the pattern of distribution in group. The coverage of seagrass in Karang tirta's coastal included into poor cathegory. Meanwhile, the seagrass bed is one of the important ecosystem in the coastal area that are habitat for some other species and carbon sinc. Physical chemical factor's water of Karang Tirta's coastal area can support the growth of seagrass well except the temperature factor that is high.